2014
DOI: 10.21273/hortsci.49.6.741
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Substrate Moisture Content on Growth and Physiological Responses of Two Landscape Roses (Rosa hybrida L.)

Abstract: A greenhouse study was conducted to quantify the irrigation requirements of two rose (Rosa hybrida L.) cultivars, RADrazz and Belinda’s Dream, which are widely valued for their ease of maintenance in landscapes, grown at four constant volumetric substrate moisture contents (SMCs) of 10%, 20%, 30%, and 40%. In both cultivars, there were no differences in growth and physiological responses between 30% and 40% SMC. In ‘RADrazz’, shoot dry weight (DW) was reduced by 25% and 86%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Studies have shown that the carnation, crimson bottlebrush, salvia, rose (Rosa spp. ), and geranium leaf gas exchange rates decreased as the SMC level decreased ( Alvarez et al, , 2011Cai et al, 2012Cai et al, , 2014Eakes et al, 1991;S anchez-Blanco et al, 2009). In our study, lower photosynthesis rates with WR-SMC for lantana, impatiens SCC and SSL, and salvia led to reductions in their shoot and/or root growth.…”
Section: Resultssupporting
confidence: 43%
“…Studies have shown that the carnation, crimson bottlebrush, salvia, rose (Rosa spp. ), and geranium leaf gas exchange rates decreased as the SMC level decreased ( Alvarez et al, , 2011Cai et al, 2012Cai et al, , 2014Eakes et al, 1991;S anchez-Blanco et al, 2009). In our study, lower photosynthesis rates with WR-SMC for lantana, impatiens SCC and SSL, and salvia led to reductions in their shoot and/or root growth.…”
Section: Resultssupporting
confidence: 43%
“…Alem et al (2015) found bract size of 'Classic Red' poinsettia (Euphorbia pulcherrima) was reduced by 53%, 47%, and 31% for the water deficit treatments. Number of flowers of 'RADrazz' rose and 'Belinda's Dream' were not different for plants maintained at 30% and 40% VWC; however, flower number was reduced by 27% and 86% for the 20% and 10% treatments for 'RADrazz' rose and by 42% and 75% for the 20% and 10% treatments for 'Belinda's Dream' rose (Cai et al, 2014). Species variability, similar to plant growth, indicates species-specific response based on adaptation features, severity of water stress, or ability to acclimate to drought.…”
Section: Resultsmentioning
confidence: 82%
“…Three sensor readings were taken at three different locations in the beaker, avoiding taking readings too close to the edge according to WaterScout SM 100 Soil Moisture Sensor product manuals. SMC calculation was SMC = (WW -DW) • 100%/1000 (Cai et al, 2012(Cai et al, , 2014. Post production treatments.…”
Section: Methodsmentioning
confidence: 99%